What are you actually measuring? A review of techniques that integrate the stress response on distinct time‐scales - Gormally, Brenna M. G.; Romero, L. Michael; Angelier, Frédéric (Functional ecology, 2020)
The field of stress physiology has rapidly expanded, particularly in those fields interested in identifying chronic stress in wild animals. Despite this expansion, stress remains difficult to assess and understand, due in large part to the temporal complexities of common stress measurement techniques. While the stress response happens on a short time‐scale, chronic stress results over longer time‐scales. Therefore, the temporal dynamics of techniques used to assess ‘stress’ need to be fully understood in order to be applied correctly. In this review, we provide information on 37 physiological and behavioural metrics that are commonly used to measure stress, especially in wild free‐living vertebrates, with a particular focus on which time‐scale they integrate stress. We organize these metrics into seven broad categories based on which physiological system they are most closely associated with (glucocorticoids, sympathetic/parasympathetic nervous system, immune, metabolic, cellular/molecular, tissue development and behaviour). We conclude by summarizing which kind of biological questions and variation each technique is most suitable for. This review will enable researchers to understand the temporal dynamics of stress measurement techniques for better design of future studies. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.